PENYULUHAN PENGGUNAAN OBAT OVER THE COUNTER (OTC) DI KELURAHAN NGAMPEL KOTA KEDIRI - Charliandri Saputra Wahab; Prayoga Feri Yuniarto; Siswidiasari, Arifani; Probosiwi, Neni (Universitas Kadiri, 2023)
Self-medication is a medication process based on complaints or symptoms up to the drug selection stage by themselves. Percentage of self-medication behavior in Kediri City increases every year so information about self-medication is needed. The class of drugs that can be used for self-medication are over the counter (OTC) drugs which are a class of over-the-counter drugs and limited over-the-counter drugs. These drugs can be purchased without a doctor's prescription, safe and effective if used according to the instructions for use. This activity aims to change the mindset and perspective of the community to be able to respond appropriately to how to use drugs by themselves. Community service activities in the form of counseling using the lecture method combined with a question and answer session, completed the pretest and posttest questionnaires, and last session is the distribution of leaflets regarding the use of OTC drugs. The target of the activity is the community in the Ngampel Village, Kediri City. There was an increase in knowledge about the use of OTC drugs in the community in Ngampel Village, Kediri City after being given counseling. We hope that after participating in counseling, people's knowledge will increase in using OTC drugs properly.